1976
DOI: 10.1159/000240818
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Zinc, Cobalt, Bromine, Rubidium and Gold in Maternal and Cord Blood Serum

Abstract: Concentrations of zinc, cobalt, bromine, rubidium and gold have been determined by neutron activation analysis in 18 maternal and umbilical cord blood sera as well as in 7 healthy non-pregnant women who served as controls. The concentrations of essential trace elements (zinc and cobalt) were significantly lower while levels of non-essential trace elements were similar (bromine and rubidium) or increased (gold) in sera of pregnant as compared to sera of non-pregnant women. The mean value of zinc in the umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Our trace metal results for both amniotic fluid and serum are in a similar range to those found in previous studies (Markowitz et al, 1955;Borglin and Heijkenskjold, 1967;Nusbaum and Zettner, 1973;Prasad et al, 1974;Alexiou et al, 1976;Jameson, 1976;Brandes et a/., 1980). The results in one recent study (Chez et al, 1978) of zinc and copper in amniotic fluid are in a similar range to our normals, but include 3 cases of high zinc concentrations at 20-22 weeks maturity; no mention is made of fetal or neonatal outcome in these cases, but the series included a large number of samples from rhesus-sensitized pregnancies, which we excluded from our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our trace metal results for both amniotic fluid and serum are in a similar range to those found in previous studies (Markowitz et al, 1955;Borglin and Heijkenskjold, 1967;Nusbaum and Zettner, 1973;Prasad et al, 1974;Alexiou et al, 1976;Jameson, 1976;Brandes et a/., 1980). The results in one recent study (Chez et al, 1978) of zinc and copper in amniotic fluid are in a similar range to our normals, but include 3 cases of high zinc concentrations at 20-22 weeks maturity; no mention is made of fetal or neonatal outcome in these cases, but the series included a large number of samples from rhesus-sensitized pregnancies, which we excluded from our study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that, in contrast with other minerals, such as cobalt, bromine, rubidium, and gold, with similar maternal and cord blood concentrations, the concentration of zinc is almost twice as high in the cord blood than the maternal blood (Alexiou et al, 1976). As previously discussed, such a concentration gradient is compatible with the existence of active placental mechanisms for the transfer of zinc.…”
Section: 53g Lipid-soluble Vitaminsmentioning
confidence: 70%